Depth resolution in sputter profiling revisited. (8th June 2016) - Hofmann, S.; Liu, Y.; Jian, W.; Kang, H.L.; Wang, J.Y.
Abstract : Based on a brief review of the well‐established framework of definitions, measurement and evaluation principles of the depth resolution in sputter profiling for interfaces, delta layers, single layers and multilayers, an extension to additional definitions is presented, which include the full‐width‐at‐half‐maximum of layer profiles and non‐Gaussian depth resolution functions as defined by the Mixing‐Roughness‐Information depth (MRI) model. Improved evaluation methods for adequate analysis of sputter depth profiles as well as improved definitions of depth resolution are introduced in order to meet new developments in ToF‐SIMS and GDOES, and in cluster ion sputtering of so‐called delta layers in organic matrices. In conclusion, the full‐width‐at‐half‐maximum definition and measurement of depth resolution, Δ z (FWHM), is found to be more appropriate than the traditional Δ z (16–84%) in order to characterize depth profiles of single layers and multilayers, because it is also valid for non‐Gaussian depth resolution functions. Copyright © 2016 John Wiley & Sons, Ltd.